News/Interview. Issue 1 (February 2016) - Kennedy, Helen; Kirk, Andy; Stander, Julian; Dalla Valle, Luciana; Borja, Mario Cortina
Abstract : News Another record‐breaking year for global temperatures? Missing millions The Census Bureau's 2016 budget is 130 million less than requested Election polls The nefarious effect of sample bias Visualisation Helen Kennedy and Andy Kirk discuss the Seeing Data project Statistically speaking How long can Pope Francis expect to live? Interview David Trafimow on a year without the null hypothesis significance test Ask a statistician What is the calorific cost of McDonald's revenue growth? Abstract : News Another record‐breaking year for global temperatures? Missing millions The Census Bureau's 2016 budget is 130 million less than requested Election polls The nefarious effect of sample bias Visualisation Helen Kennedy and Andy Kirk discuss the Seeing Data project Statistically speaking How long can Pope Francis expect to live? Interview David Trafimow on a year without the null hypothesis significance test Ask a statistician What is the calorific cost of McDonald's revenue growth?